Iron beans in Rwanda: crop development and delivery experience - Mulambu, J.; Andersson, Meike S.; Palenberg, M.; Pfeiffer, Wolfgang H.; Saltzman, Amy; Birol, Ekin; Oparinde, A.; Boy, Erick; Asare-Marfo, Dorene; Lubobo, Antoine Kanyenga; Mukankusi, Clare Mugisha; Nkalubo, Stanley T. (Rural Outreach Program, 2017)
HarvestPlus and its partners have successfully developed and delivered iron bean varieties to more than one million farming households in Rwanda, DRC, and Uganda to help combat the adverse health effects of iron deficiency widespread in these countries. Focusing primarily on Rwanda, this chapter summarizes the country, nutritional and consumer background, crop development, release, and delivery of iron bean varieties and synthesizes lessons learned and future challenges.